Density functional theory calculation of the electronic structure of Ba0.5Sr0.5TiO3: Photoluminescent properties and structural disorder - Longo, Elson [UNESP]; Orhan, E. [UNESP]; Pontes, F. M.; Pinheiro, C. D.; Leite, E. R.; Varela, José Arana [UNESP]; Pizani, P. S.; Boschi, T. M.; Lanciotti, F.; Beltrán, A.; Andrés, J. (American Physical Society (APS), 2004)
First-principles quantum-mechanical techniques, based on density functional theory (B3LYP level) were employed to study the electronic structure of ordered and deformed asymmetric models for Ba0.5Sr 0.5TiO3. Electronic properties are analyzed and the relevance of the present theoretical and experimental results on the photoluminescence behavior is discussed. The presence of localized electronic levels in the band gap, due to the symmetry break, would be responsible for the visible photoluminescence of the amorphous state at room temperature. Thin films were synthesized following a soft chemical processing. Their structure was confirmed by x-ray data and the corresponding photoluminescence properties measured.
Keywords: amorphous titanate; barium; strontium; titanium derivative; unclassified drug; crystal structure; density functional theory; electronics; energy; film; photoluminescence; quantum mechanics; room temperature; synthesis